Effects of granular and liquid fertilizers on phytoplankton under experimental pond condition (Bangladesh Journal of Botany, 2015)
Under the experimental pond condition, three treatments of fertilizers on phytoplankton were carried out. The first treatment was with granular fertilizers (GF), and the second and third treatments were with liquid fertilizer A (LFA), low concentration and liquid fertilizer B (LFB), high concentration, respectively. The mean pH and the average transparency of the water varied significantly among different treatments (p < 0.05). Gross and net productivity in the LFB-treated ponds were higher than those observed in the two other treatments (p < 0.05). In addition, the bacillariophytes did not change significantly among treatments (p < 0.05). However, the chlorophytes increased in the LFB treatment, and the cyanophytes were increased in the GF treatment (p < 0.05). DOI: http://dx.doi.org/10.3329/bjb.v43i2.21670 Bangladesh J. Bot. 43(2): 175-181, 2014 (September)